"Is It Worth Knowing?" Focus Group Participants' Perceived Utility of Genomic Preconception Carrier Screening. Issue 1 (21st June 2015) - Schneider, Jennifer L.; Goddard, Katrina A. B.; Davis, James; Wilfond, Benjamin; Kauffman, Tia L.; Reiss, Jacob A.; Gilmore, Marian; Himes, Patricia; Lynch, Frances L.; Leo, Michael C.; McMullen, Carmit
Abstract: As genome sequencing technology advances, research is needed to guide decision‐making about what results can or should be offered to patients in different clinical settings. We conducted three focus groups with individuals who had prior preconception genetic testing experience to explore perceived advantages and disadvantages of genome sequencing for preconception carrier screening, compared to usual care. Using a discussion guide, a trained qualitative moderator facilitated the audio‐recorded focus groups. Sixteen individuals participated. Thematic analysis of transcripts started with a grounded approach and subsequently focused on participants' perceptions of the value of genetic information. Analysis uncovered two orientations toward genomic preconception carrier screening: "certain" individuals desiring all possible screening information; and "hesitant" individuals who were more cautious about its value. Participants revealed valuable information about barriers to screening: fear/anxiety about results; concerns about the method of returning results; concerns about screening necessity; and concerns about partner participation. All participants recommended offering choice to patients to enhance the value of screening and reduce barriers. Overall, two groups of likely users of genome sequencing for preconception carrier screening demonstrated different perceptions of the advantages or disadvantages of screening, suggesting tailored approaches to education, consent, and counseling may be warranted with each group.